Irrigation water conservation: opportunities and limitations in Colorado: a report of the Agricultural Water Conservation Task Force - Smith, D. H., author; Klein, Kathleen, author; Bartholomay, Richard, author; Broner, Israel, author; Cardon, G. E., author; Frasier, W. M., author; Kuharich, Rod, author; Lile, D. C., author; Gross, Mike, author; Parker, Dan, author; Simpson, Hal, author; Wilkinson, Eric, author; et al. (Colorado State University. Libraries, 1996)
The implications of irrigation water conservation are an important consideration, especially in watershed basins where water is derived from surface diversions or shallow alluvial aquifers. Under these conditions, wide-scale adoption of conservation practices designed to increase diversion efficiencies has the potential of altering basin hydrology by reducing the magnitude of return flows. Conversely, the implications of agricultural water conservation in areas of the eastern plains, where deep aquifers are the source of irrigation water, are largely positive because of the overall effect of prolonging the usable life of the aquifer and, thus, the economic viability of the region. Because of variation in potential impacts of irrigation water conservation, the task force concluded that policy initiatives designed to implement conservation should be based on how water is used at the basin level rather that the individual farm level. Also, impacts of water conservation strategies on interstate compact obligations must be considered.
October 1996.
Keywords: Irrigation efficiency -- Colorado; Irrigation -- Colorado -- Management; Water conservation -- Colorado